Technology-Enabled Arabic Language Learning: Opportunities, Challenges and Future Directions in the Digital Era - K. M. A. Ahamed Zubair (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
The rapid advancement of digital technology has fundamentally transformed language education, creating new paradigms for teaching and learning Arabic in the digital era. This article examines the opportunities and challenges of technology-enabled Arabic language learning through a comprehensive literature review of contemporary research from multiple geographical contexts, including Indonesia, India, and Algeria. The study investigates four primary technological modalities: e-learning platforms, mobile applications, social media integration, and game-based learning. Findings indicate that technology significantly enhances accessibility, provides flexible learning opportunities, offers diverse multimedia resources, and increases learner engagement through interactive features. However, substantial challenges persist, including uneven content quality, inadequate technological infrastructure, limited social interaction, lack of verified educational materials, and insufficient teacher training. The research synthesizes successful implementation strategies from various educational contexts and proposes an integrated framework addressing pedagogical, technical, and cultural dimensions. The study concludes that while technology offers transformative potential for Arabic language education, optimal outcomes require balanced integration of digital tools with direct human interaction, culturally authentic materials, and systematic teacher development programs.